Fungsi Ritual Tari Maulud Lengger Dalam Upacara Suran Di Desa Gandu Kecamatan Tembarak Kabupaten Temanggung - Dilla, Anim Kartika; MD, Slamet (Institut Seni Indonesia Surakarta, 2021)
This study explores the Maulud Lengger dance in the Suran ceremony. The problem is focused on discussing the form and function of the ritual. The problem of form is analyzed using Slamet MD's theory, while the problem of ritual function is analyzed using Soedarsono's theory. This research uses qualitative research methods. Data collection techniques were carried out by means of observation, interviews, and literature studies. The results of the study indicate that the Maulud Lengger dance has an important role in the implementation of the Suran ceremony, which is believed to have a major influence on the survival of the Gandu Village community. In terms of the form of the performance, this dance contains religious elements that can be seen from the poems that are played.